Pemanfaatan Media Gambar dalam Meningkatkan Keterampilan Berbahasa Pemelajar BIPA - Syakir, Akhmad; Istiqamah, Istiqamah; Leha, Noor; Daviria, Eqmi Avi; Fitri, Diani; Putri, Diani (Universitas Pahlawan Tuanku Tambusai, 2026)
Teaching Indonesian to Speakers of Other Languages (BIPA) requires continuous innovation to maintain motivation and increase the active participation of learners. This community service activity aims to introduce and implement the use of two interactive media, namely